The Legal Construction of Criminal Liability of Sharia Bank Officials in Cases of Fictitious Credit as an Abuse of Authority and Breach of Official Trust: A Case Study of the Pangkalpinang District Court Decision Number 31/Pid.Sus-TPK/2024/PN PGP - Fara Deni; Muhamad Adytia Sunggara; Junaidi Abdillah (GoAcademica Research & Publishing, 2026)
This research aims to analyze the reasoning of judges in the Ruling of the Pangkalpinang District Court Number 31/Pid.Sus-TPK/2024/PN PGP concerning fictitious financing cases in Islamic banking, positioning it within the spectrum between a formalistic approach and substantive justice. This research employs a normative legal research method with statutory, conceptual, and case approaches, analyzed qualitatively through tracing the ratio decidendi of the decisions and comparing them with doctrines of economic criminal law and banking law. The results indicate that the panel of judges has successfully proven the elements of corruption offenses normatively, particularly the abuse of authority and state financial losses; however, the reasoning applied remains predominantly formalistic. The main findings of this research reveal that judges have not deeply elaborated on the concepts of fiduciary duty, the trust of office, and substantive parameters for distinguishing between administrative errors and official crimes. The contribution of this research lies in the development of a more substantive judicial reasoning framework by integrating the principles of prudence, abuse of authority, and the specific characteristics of Islamic banking, thereby enabling criminal law to function proportionally as an instrument for protecting public interests and substantive justice.